Fungicidal control of the most common onion mycoses during the growing season - Borzykh, O.; Sergienko, V.; Dzham, M.; Shyta, O.; Mykhaylenko, S. (Quarantine and plant protection, 2023)
Goal. To investigate the effectiveness of fungicidal control of the most common onion diseases during the growing season. Methods. Informational and analytical (collection of materials and analysis of literary sources), field research (setting up experiments, carrying out treatments and records of plant damage by diseases, monitoring the development of plants, harvesting), phytopathological (determination and identification of pathogens), mathematical and statistical (processing of results studies). Experiments were conducted on different varieties and hybrids using modern fungicides with different active substances. Results. During the years of research, onion crops were dominated by mycoses, namely, peronosporosis, alternaria, stemphylliosis, and fusarium wilt. Downy mildew and leaf spots were observed on all varieties and hybrids. The investigated fungicides most effectively controlled the development of downy mildew of onions. Their efficiency during the growing season averaged 55.1—100%, depending on the drug, the degree of disease development and the variety. The highest effectiveness against downy mildew of onions was provided by fungicides Fandango 200 ES, KE (fluoxystrobin, 100 g/l + proteoconazole, 100 g/l) at the rate of 1.25 l/ ha and Signum VG (boskalid, 267 g/ kg + pyraclostrobin, 67 g/ kg) — 1.5 kg/ ha. Fungicides were 45.8—89.1% effective against leaf spots (alternaria and stemphyllosis), 57.9—70.5% against fusarium wilt. Treatments with fungicides, due to the reduction of plant damage by diseases, contributed to the increase in onion yield by 1.3—6.9 t/ha, depending on the variety and preparation. Among the studied varieties, the highest yield was obtained on the Medusa variety (40.7 t/ha), among fungicides, the highest yield increase was provided by Fandango 200 ES, KE fungicide (1.25 l/ha). Conclusions. Fungicides effectively controlled the main mycoses of onion (peronosporosis, alternariosis, stemphyllosis and fusarium wilt) during the growing season. The effectiveness of fungicides against onion diseases was 45.8—100%, depending on the type of disease, drug and crop variety. The highest protective effect of fungicides was provided against downy mildew of onions. The yield of the researched varieties and hybrids increased by an average of 5—25% due to the reduction of plant damage by diseases. The highest technical efficiency against identified diseases and increase in onion yield was obtained by using Fandango 200 ES, KE fungicide with a consumption rate of 1.25 l/ha.